Factors influencing internet based ICT adoptions intention among SMES in Malaysia - Mohd Nor Abd Muhaimin, Mohd Yusof (2013)
In Malaysia, SMEs play a vital role and important in Malaysian economy. It is considered to be the backbone of industrial development in the country. SMEs plays important role in generating employment, enhancing the quality of human resources, nurturing a culture of entrepreneurship, supporting the large scale industries and opening up new business opportunities. Currently Malaysian SMEs account for 59% of employments and their contribution to exports is at 19% , and this is expected to grow to 62% of employments with 25% exports contribution by 2020 (Borneo Post, 2012) The emergence of information and communications technologies (ICTs) has affected many industries and organizations. It is undeniable that ICT are transforming the industries and fueling the growth of the global economy. In its effort to transform Malaysia economy from a commodity-based producing nation to being a manufacturer of industrial products and more recently knowledge based economy, the government is putting greater emphasis on ICT. Notwithstanding the many efforts undertaken by Malaysian governments to promote ICT adoption among SMEs across different types of industries, many of them failed to reap this benefit evenly. This problem is prevalent among the SMEs in the Asia Pacific region and Malaysia is no exception. Realizing the prominence of SMEs as a main contributor to the country’s GDP and employment as well as the ICT as an enabler to leapfrog Malaysia to achieve Vision 2020, this study sought to understand and identify the factor that influences the SMEs towards Internet-based ICT adoption in Malaysia. Therefore this study presents extended Technology Acceptance Model (TAM) that integrates Theory of Planned Behavior (TPB) into the research model to examine what determines Internet-based ICT adoption among Malaysian SMEs. The proposed model was empirically tested using data collected from a survey conducted. The study involved 103 SME businesses throughout the state in Malaysia using questionnaire survey instrument. The result of this study supports the theoretical framework as well as clarifies and extend it. The findings also includes some suggestion and recommendation to further promote Internet-based ICT adoption among the SMEs